AN ANALYSIS STUDNTS’ ABILITY IN READING COMPREHENSION AT THE SECOND SEMESTER AT EDUCATION PROGRAM OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Anggun Cahaya Febrianti; Fetriani (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The research was aim to describe about students’ ability levels in reading comprehension at the second semester Muhammadiyah University of Bengkulu. This method of this study was descriptive qualitative. The research instrument was a reading comprehension test to show the students’ reading ability based on the theory of (Roe, 2011). There were; main idea, specific information, reference, inference, and vocabulary. The results of the study, it was only analysis reading ability in vocabulary got very high score with the percentage 90.90%. And the four rest abilities got very low score. To be considered, reading is an important part for English language students. It is obvious that we have to be good reading ability in reading comprehension because reading is each part four language skills. The researcher are hoped to teach the students about strategy in reading subject, specially to improve reading ability in main idea, specific information, reference, inference. Keywords: Reading Ability, Levels, Comprehension